An audit of PMTCT services at a regional hospital in South Africa - Emako Orie; Pavel P. Songca; Jagidesa Moodley (South African Family Practice)
Prevention of mother-to-child transmission (PMTCT) is a major intervention world-wide in the fight against the HIV pandemic, and has resulted in markedly reduced rates of mother-to-child transmission rates in well-resourced countries.